Sensor fusion for complex articulated body tracking applied in rowing - Ruffaldi, E.; Peppoloni, L.; Filippeschi, A. (Proceedings of the Institution of Mechanical Engineers, Part P: Journal of Sports Engineering and Technology, 2015)
This paper presents a sensor fusion model for integrating wearable inertial measures with sensors in the environment. This approach is designed and tested to support body motion tracking of rowing in indoor and outdoor environments. This paper presents the approach based on a complex kinematic model and Unscented Kalman filtering. The approach is validated in an indoor setup based on the SPRINT rowing system by comparison against results obtained from a commercial motion capture system, thus providing future directions for the assessment of rowers` performance on an instrumented boat.